Preparation method of high-activity iron-based-sulfide-assistant composite material as well as product and application thereof
By preparing highly reactive iron-sulfide-adjuvant composite materials, the secondary pollution problem of iron-based by-products during phenol wastewater treatment in industrial wastewater is solved, and the treatment cost is reduced, achieving the effect of efficient removal of organic pollutants.
Patent Information
- Application Number
- CN202510091425.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art produces unnecessary iron-based by-products when treating phenol wastewater in industrial wastewater, resulting in secondary pollution of the environment. The economic cost and energy consumption of hydrothermal synthesis of sulfides are high when combined with iron-based materials.
The high-active iron-based-sulfide-adjuvant composite material is prepared by mixing the iron-based material with the sulfide-adjuvant solution, sonication, heating reaction and cooling, and high-active composite material is prepared. The additives are selected from sulfites, sodium borohydride and manganese oxide to accelerate the reaction process and reduce costs.
It has achieved efficient removal of organic pollutants, especially phenol, under acidic conditions, with a degradation rate of 90-100%, while reducing economic and energy consumption costs and avoiding secondary pollution to the environment.
Smart Images

Figure CN119909714A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical technology, and in particular relates to a preparation method of a high-activity iron-based-sulfide-auxiliary agent composite material, a product thereof and an application thereof. Background Art
[0002] With the continuous advancement of science and technology, the acceleration of industrial development and the overuse of natural resources, water treatment has become an important issue of concern to the world. Phenol wastewater in industrial wastewater is a typical organic wastewater that is difficult to degrade. If it is not treated in time and discharged into the environment, it will cause irreparable damage to the environment. Therefore, the treatment of phenol wastewater is of great significance to the environment and social progress of human survival. Fenton technology plays a very effective role in treating wastewater, with the characteristics of high efficiency, cleanliness and economic benefits. However, in industrialization, after entering the neutralization tank, some unnecessary iron-based by-products are produced as the reaction proceeds, causing secondary pollution to the environment. Previously, hydrothermally synthesized sulfides can be compounded with iron-based materials, and the composite material has high activity, but the economic cost and energy consumption required are high. Therefore, it is particularly important to develop a highly active iron-based-sulfide-auxiliary composite material for treating these iron-based by-products. Summary of the invention
[0003] In view of the above technical problems, the present invention proposes a preparation method of a highly active iron-based-sulfide-additive composite material, its product and application, so as to solve the secondary pollution and cost problems in the Fenton technology for treating wastewater.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] One of the purposes of the present invention is to provide a method for preparing a high-activity iron-based-sulfide-additive composite material, comprising the following steps: adding an iron-based material to a sulfide-additive solution, ultrasonically treating, heating for reaction, and cooling to obtain a high-activity iron-based-sulfide-additive composite material; wherein the additive in the sulfide-additive solution is selected from one of sulfite, sodium borohydride and manganese oxide.
[0006] The present invention utilizes the chemical bonding between iron-based materials and sulfides, and then adds a strong reducing agent to prepare a highly active iron-based-sulfide-auxiliary agent composite material for removing organic pollutants under acidic conditions; the chemical bonding between the iron-based material and the sulfide can construct an acidic microenvironment on the surface of the iron-based material, thereby ensuring the stable circulation of iron ions within a local microenvironment, and after the strong reducing agent is added, this process can be accelerated, thereby achieving high efficiency in degrading wastewater.
[0007] Since the activity of commercial sulfide will inevitably decrease, the present invention adds an auxiliary agent to the sulfide to make up for the lack of activity reduction while reducing economic costs and energy costs. While the heterogeneous Fenton reaction system is used to truly treat wastewater byproducts, it replaces the recycling of iron sources in the Fenton reaction, reduces costs and avoids unnecessary secondary pollution to the environment, which has important scientific significance in the field of environment.
[0008] Furthermore, the specific preparation method of the iron-based material includes: adding an iron source and hydrogen peroxide into water, stirring evenly, adjusting the pH to neutral, standing, centrifuging, and drying to obtain the iron-based material.
[0009] Furthermore, the usage ratio of the iron source, hydrogen peroxide and water is (10-1000) mg: (1-20) mL: (10-1000) mL; and / or
[0010] The iron source is selected from one of ferrous oxide, ferric oxide, ferroferric oxide, ferric chloride, ferric sulfate and ferrous sulfate; and / or
[0011] The reagent used to adjust the pH is sulfuric acid; and / or
[0012] The standing time is 1-1000 min.
[0013] Furthermore, the specific preparation method of the sulfide-additive solution includes: adding a molybdenum source and a sulfur source into water, adding an additive after ultrasonic treatment, and continuing ultrasonic treatment to obtain a sulfide-additive solution.
[0014] Furthermore, the molybdenum source is selected from one or more of ammonium molybdate, sodium molybdate, molybdenum trioxide, molybdenum dioxide and molybdenum powder; and / or
[0015] The sulfur source is selected from one or more of thioacetamide, thiourea, sulfur powder and sodium sulfide; and / or
[0016] The molybdenum source, sulfur source, water and auxiliary agent are used in a ratio of (1-1000) mg: (1-2000) mg: (10-100) mL: (1-1000) mg; and / or
[0017] The ultrasonic time is 1-60 min.
[0018] Furthermore, the ultrasonic treatment time is 1-100 min.
[0019] Furthermore, the heating reaction conditions are: reacting at 60-100° C. for 1-5 hours.
[0020] The second object of the present invention is to provide a high-activity iron-based-sulfide-auxiliary agent composite material prepared by the above-mentioned preparation method.
[0021] The third object of the present invention is to provide a high-activity iron-based-sulfide-auxiliary agent composite material for use in removing organic pollutants in wastewater.
[0022] The fourth object of the present invention is to provide a method for removing organic pollutants, comprising the following steps: putting the highly active iron-based-sulfide-auxiliary composite material into wastewater containing organic pollutants, adding an initiator, stirring, and achieving the removal of organic matter; wherein,
[0023] The organic pollutant is phenol, and the concentration of phenol in the wastewater is 1-2000 mg / L;
[0024] The initiator is 30wt% hydrogen peroxide;
[0025] The input amount of the high-activity iron-based-sulfide-auxiliary composite material is 300 mg / L;
[0026] The wastewater containing organic pollutants is acidic.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] 1. Compared with the traditional wastewater treatment system, the present invention solves the secondary pollution problem of by-products. After resource utilization, it can achieve excellent effect of removing pollutants in wastewater again;
[0029] 2. The amount of catalyst added in the present invention is relatively small, and the catalyst is magnetic, so the recovery is convenient and simple, and secondary pollution to the environment can be avoided.
[0030] 3. The present invention synthesizes a highly active iron-based-sulfide-auxiliary agent composite material, which has a pollutant removal efficiency of 90-100% removal of phenol within 10 minutes, and can replace the iron source used in the Fenton technology to a certain extent when removing wastewater COD (chemical oxygen demand), providing the possibility of using heterogeneous Fenton reaction to treat wastewater at low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0032] Figure 1 This is a comparison chart of the degradation effects of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2 on phenol;
[0033] Figure 2 This is a comparison chart of the degradation effects of the products prepared in Examples 1-3 and Comparative Examples 3-4 on phenol;
[0034] Figure 3 This is a comparison chart of the degradation effects of the product prepared in Example 3 and ferrous oxide when mixed in different proportions as a catalyst on COD. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] The embodiment of the present invention provides a method for preparing a high-activity iron-based-sulfide-additive composite material, comprising the following steps:
[0041] 1) Preparation of iron-based materials;
[0042] 2) preparing a sulfide-additive solution;
[0043] 3) adding the iron-based material to the sulfide-additive solution, subjecting it to ultrasonic treatment, heating it for reaction, cooling it after the reaction is completed, and drying it to obtain a highly active iron-based-sulfide-additive composite material.
[0044] In some embodiments, in step 1), the specific preparation method of the iron-based material includes: adding an iron source and hydrogen peroxide to a beaker filled with water, stirring with a magnetic bar to obtain a uniform solution; adjusting the pH of the uniform solution to neutral, stopping stirring, standing, centrifuging, and drying to obtain the iron-based material.
[0045] The usage ratio of the iron source, hydrogen peroxide and water is (10-1000) mg: (1-20) mL: (10-1000) mL. For example, in the following preferred embodiments of the present invention, the usage ratio of the iron source, hydrogen peroxide and water can be selected as 300 mg: 20 mL: 100 mL.
[0046] The iron source is selected from one of ferrous oxide, ferric oxide, ferroferric oxide, ferric chloride, ferric sulfate and ferrous sulfate. Exemplarily, in the following preferred embodiments of the present invention, the iron source can be ferrous oxide.
[0047] The stirring time is 1-100 hours. For example, in the following preferred embodiments of the present invention, the stirring time can be selected as 24 hours.
[0048] The reagent used for adjusting pH is sulfuric acid.
[0049] The standing time is 1-1000 min. For example, in the following preferred embodiments of the present invention, the standing time can be selected as 180 min.
[0050] In some embodiments, in step 2), the specific preparation method of the sulfide-additive solution includes: adding a molybdenum source and a sulfur source into a beaker containing water, adding an additive after ultrasonication, and continuing ultrasonication to obtain a sulfide-additive solution.
[0051] The molybdenum source is selected from one or more of ammonium molybdate, sodium molybdate, molybdenum trioxide, molybdenum dioxide and molybdenum powder. For example, in the following preferred embodiments of the present invention, the molybdenum source can be selected from sodium molybdate.
[0052] The sulfur source is selected from one or more of thioacetamide, thiourea, sulfur powder and sodium sulfide.
[0053] The auxiliary agent in the sulfide-auxiliary agent solution is selected from one of sulfite, sodium borohydride and manganese oxide. Exemplarily, in the following preferred embodiments of the present invention, the auxiliary agent can be selected from sulfite, sodium borohydride or manganese oxide.
[0054] The molybdenum source, sulfur source, water and auxiliary agent are used in a ratio of (1-1000) mg: (1-2000) mg: (10-100) mL: (1-1000) mg. Exemplarily, in the following preferred embodiments of the present invention, the molybdenum source, sulfur source, water and auxiliary agent can be used in a ratio of (400-800) mg: (200-500) mg: (100) mL: (100-300) mg.
[0055] The ultrasonic time is 1-60 min. For example, in the following preferred embodiments of the present invention, the ultrasonic time is 60 min.
[0056] In some embodiments, in step 3), the ultrasonic treatment time is 1-100 min. Exemplarily, in the following preferred embodiments of the present invention, the ultrasonic treatment time can be selected to be 30 min.
[0057] In some embodiments, in step 3), the heating reaction is carried out at 60-100° C. for 1-5 hours. For example, in the following preferred embodiments of the present invention, the heating reaction can be carried out at 80° C. for 4 hours.
[0058] The above preparation method can be used to prepare a highly active iron-based-sulfide-auxiliary composite material. For example, a highly active ferroferric oxide-ammonium thiomolybdate-sulfite composite material is constructed. By chemically combining the byproduct ferroferric oxide with ammonium thiomolybdate under the condition of adding sulfite, an acidic microenvironment can be constructed on the surface of ferroferric oxide, thereby ensuring the stable circulation of iron ions in a local microenvironment. After adding sulfite, this process can be accelerated, thereby achieving high efficiency in degrading wastewater.
[0059] The highly active iron-based-sulfide-auxiliary composite material can be used to remove organic pollutants in wastewater, wherein the organic matter can be phenol. The highly active iron-based-sulfide-auxiliary composite material prepared by the present invention can also reduce COD in wastewater.
[0060] The method for removing organic pollutants comprises the following steps: putting a high-activity iron-based-sulfide-auxiliary agent composite material into wastewater containing organic pollutants, adding an initiator, stirring, and achieving removal of organic matter.
[0061] In some embodiments, the organic pollutant is phenol, and the concentration of the phenol in the wastewater is 1-2000 mg / L; illustratively, in the following preferred embodiments of the present invention, the concentration of the phenol can be selected to be 20 mg / L.
[0062] In some embodiments, the initiator is 30 wt% hydrogen peroxide; the amount of hydrogen peroxide added to 100 mL of wastewater is 250 μL;
[0063] In some embodiments, the input amount of the high-activity iron-based-sulfide-additive composite material is 300 mg / L.
[0064] In some embodiments, the wastewater is acidic wastewater. For example, in the following preferred embodiments of the present invention, the pH of the wastewater can be set to 4.
[0065] The raw materials used in the present invention are all purchased from the market.
[0066] The technical solution of the present invention is further illustrated by the following embodiments.
[0067] Example 1
[0068] A method for preparing a highly active iron-based-sulfide-additive composite material comprises the following steps:
[0069] 1) Preparation of iron-based materials:
[0070] 300 mg of ferrous oxide and 20 mL of hydrogen peroxide were added to a beaker containing 100 mL of water, and stirred with a magnetic stirrer for 24 hours to obtain a uniform solution; the pH of the uniform solution was adjusted to neutral with sulfuric acid, and then stirring was stopped, and the solution was allowed to stand for 180 minutes, centrifuged, and dried to obtain ferrosoferric oxide;
[0071] 2) Preparation of sulfide-additive solution: 400 mg sodium molybdate and 200 mg thioacetamide were added to a beaker containing 100 mL water, and after ultrasonication for 60 min, 100 mg sulfite was added to the beaker, and ultrasonication was continued for 60 min to obtain ammonium thiomolybdate-sulfite solution;
[0072] 3) After ultrasonically treating the ferroferric oxide and ammonium thiomolybdate-sulfite solution for 30 minutes, the solution was placed in a water bath and mechanically stirred for reaction at 80° C. for 4 hours. After the reaction was completed, the solution was cooled and dried to obtain a highly active ferroferric oxide-ammonium thiomolybdate-sulfite composite material.
[0073] Example 2
[0074] A method for preparing a highly active iron-based-sulfide-additive composite material comprises the following steps:
[0075] 1) Preparation of iron-based materials:
[0076] 300 mg of ferrous oxide and 20 mL of hydrogen peroxide were added to a beaker containing 100 mL of water, and stirred with a magnetic stirrer for 24 hours to obtain a uniform solution; the pH of the uniform solution was adjusted to neutral with sulfuric acid, and then stirring was stopped, and the solution was allowed to stand for 180 minutes, centrifuged, and dried to obtain ferrosoferric oxide;
[0077] 2) Preparation of sulfide-additive solution: 800 mg of ammonium molybdate and 500 mg of thiourea were added to a beaker containing 100 mL of water, and after ultrasonication for 60 min, 300 mg of sodium borohydride was added to the beaker, and ultrasonication was continued for 60 min to obtain an ammonium thiomolybdate-sodium borohydride solution;
[0078] 3) After ultrasonically treating the ferroferric oxide and ammonium thiomolybdate-sodium borohydride solution for 30 minutes, the solution was placed in a water bath and mechanically stirred for reaction at 80° C. for 4 hours. After the reaction was completed, the solution was cooled and dried to obtain a highly active ferroferric oxide-ammonium thiomolybdate-sodium borohydride composite material.
[0079] Example 3
[0080] A method for preparing a highly active iron-based-sulfide-additive composite material comprises the following steps:
[0081] 1) Preparation of iron-based materials:
[0082] 300 mg of ferrous oxide and 20 mL of hydrogen peroxide were added to a beaker containing 100 mL of water, and stirred with a magnetic stirrer for 24 hours to obtain a uniform solution; the pH of the uniform solution was adjusted to neutral with sulfuric acid, and then stirring was stopped, and the solution was allowed to stand for 180 minutes, centrifuged, and dried to obtain ferrosoferric oxide;
[0083] 2) Preparation of sulfide-additive solution: 600 mg of ammonium molybdate and 300 mg of sulfur powder were added to a beaker containing 100 mL of water, and after ultrasonication for 60 min, 200 mg of manganese oxide was added to the beaker, and ultrasonication was continued for 60 min to obtain an ammonium thiomolybdate-manganese oxide solution;
[0084] 3) The ferroferric oxide and ammonium thiomolybdate-manganese oxide solution were ultrasonically treated for 30 minutes and then placed in a water bath, and mechanically stirred for reaction at 80° C. for 4 hours. After the reaction was completed, the solution was cooled and dried to obtain a highly active ferroferric oxide-ammonium thiomolybdate-manganese oxide composite material.
[0085] Comparative Example 1
[0086] A method for preparing a highly active iron-based-sulfide composite material comprises the following steps:
[0087] 1) Preparation of iron-based materials:
[0088] 300 mg of ferrous oxide and 20 mL of hydrogen peroxide were added to a beaker containing 100 mL of water, and stirred with a magnetic stirrer for 24 hours to obtain a uniform solution; the pH of the uniform solution was adjusted to neutral with sulfuric acid, and then stirring was stopped, and the solution was allowed to stand for 180 minutes, centrifuged, and dried to obtain ferrosoferric oxide;
[0089] 2) Preparation of sulfide-additive solution: 400 mg sodium molybdate and 200 mg thioacetamide were added to a beaker containing 100 mL water, and then ultrasonicated for 60 min to obtain ammonium thiomolybdate solution;
[0090] 3) The ferrosoferric oxide and ammonium thiomolybdate solution were ultrasonically treated for 30 minutes and then placed in a water bath, and mechanically stirred for reaction at 80° C. for 4 hours. After the reaction was completed, the solution was cooled and dried to obtain a highly active ferrosoferric oxide-ammonium thiomolybdate composite material.
[0091] Comparative Example 2
[0092] A method for preparing an iron-based material comprises the following steps:
[0093] Add 300 mg of ferrous oxide and 20 mL of hydrogen peroxide into a beaker containing 100 mL of water, stir with a magnetic stirrer for 24 hours, and then obtain a uniform solution; adjust the pH of the uniform solution to neutral with sulfuric acid, stop stirring, let stand for 180 minutes, centrifuge, and dry to obtain ferrosoferric oxide.
[0094] Comparative Example 3
[0095] A method for preparing a highly active iron-based-sulfide-additive composite material comprises the following steps:
[0096] 1) Preparation of iron-based materials:
[0097] 300 mg of ferrous oxide and 20 mL of hydrogen peroxide were added to a beaker containing 100 mL of water, and stirred with a magnetic stirrer for 24 hours to obtain a uniform solution; the pH of the uniform solution was adjusted to neutral with sulfuric acid, and then stirring was stopped, and the solution was allowed to stand for 180 minutes, centrifuged, and dried to obtain ferrosoferric oxide;
[0098] 2) Preparation of sulfide-additive solution: 400 mg sodium molybdate and 200 mg thioacetamide were added to a beaker containing 100 mL water, and after ultrasonication for 60 min, 100 mg methanol was added to the beaker, and ultrasonication was continued for 60 min to obtain ammonium thiomolybdate-methanol solution;
[0099] 3) After ultrasonically treating the ferrosoferric oxide and ammonium thiomolybdate-methanol solution for 30 minutes, the solution was placed in a water bath and mechanically stirred for reaction at 80° C. for 4 hours. After the reaction was completed, the solution was cooled and dried to obtain a highly active ferrosoferric oxide-ammonium thiomolybdate-methanol composite material.
[0100] Comparative Example 4
[0101] A method for preparing a highly active iron-based-sulfide-additive composite material comprises the following steps:
[0102] 1) Preparation of iron-based materials:
[0103] 300 mg of ferrous oxide and 20 mL of hydrogen peroxide were added to a beaker containing 100 mL of water, and stirred with a magnetic stirrer for 24 hours to obtain a uniform solution; the pH of the uniform solution was adjusted to neutral with sulfuric acid, and then stirring was stopped, and the solution was allowed to stand for 180 minutes, centrifuged, and dried to obtain ferrosoferric oxide;
[0104] 2) Preparation of sulfide-additive solution: 400 mg sodium molybdate and 200 mg thioacetamide were added to a beaker containing 100 mL water, and after ultrasonication for 60 min, 100 mg ethanol was added to the beaker, and ultrasonication was continued for 60 min to obtain ammonium thiomolybdate-ethanol solution;
[0105] 3) After ultrasonically treating the ferrosoferric oxide and ammonium thiomolybdate-methanol solution for 30 minutes, the solution was placed in a water bath and mechanically stirred for reaction at 80° C. for 4 hours. After the reaction was completed, the solution was cooled and dried to obtain a highly active ferrosoferric oxide-ammonium thiomolybdate-ethanol composite material.
[0106] Application Example 1
[0107] The products prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used as catalysts for a degradation experiment, which specifically included the following steps: 100 mL of wastewater to be treated with a pH of 4, wherein the concentration of phenol was 20 mg / L, the amount of catalyst added was 30 mg, 250 μL of 30 wt % hydrogen peroxide was added to initiate the reaction, and the mixture was stirred.
[0108] Figure 1 The comparison diagram of the degradation effect of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2 on phenol shows that the byproduct ferroferric oxide produced by the Fenton reaction is compounded with ammonium thiomolybdate and sulfite, and phenol can be efficiently degraded within 10 minutes, and the degradation rate reaches 99%, while the degradation rate of the material with only ammonium thiomolybdate compounded with ferroferric oxide is less than 20%, and the uncompounded ferroferric oxide can hardly achieve the degradation of phenol. It shows that under the action of sulfite, the composite modification of ammonium thiomolybdate on ferroferric oxide has higher activity, further showing the importance of sulfite.
[0109] Application Example 2
[0110] The products prepared in Examples 1-3 and Comparative Examples 3-4 were used as catalysts for degradation experiments, which specifically included the following steps: 100 mL of wastewater to be treated with a pH of 4, in which the concentration of phenol was 20 mg / L, the amount of catalyst added was 30 mg, 250 μL of 30 wt % hydrogen peroxide was added to initiate the reaction, and stirred.
[0111] Figure 2The comparison diagram of the degradation effect of the products prepared in Examples 1-3 and Comparative Examples 3-4 on phenol shows that the compounding of ammonium thiomolybdate and sulfite, sodium borohydride and manganese oxide on the ferroferric oxide produced by the Fenton reaction can efficiently degrade phenol within 10 minutes, and the degradation rate reaches more than 90%, while the compounding of methanol and ethanol on ferroferric oxide can hardly achieve the degradation of phenol. It shows that only under the action of sulfite, sodium borohydride and manganese oxide can the compound modification of ammonium thiomolybdate on ferroferric oxide have higher activity, further showing the importance of sulfite, sodium borohydride and manganese oxide additives.
[0112] Application Example 3
[0113] The product prepared in Example 3 and ferrous oxide were used as catalysts for a degradation experiment, which specifically included the following steps: 100 mL of wastewater to be treated with a pH of 4, wherein the COD concentration was 1000 mg / L, the total amount of catalyst added was 30 mg, 250 μL of 30 wt % hydrogen peroxide was added to initiate the reaction, and the reaction was stirred.
[0114] Among them, in 30 mg of the catalyst, the mass ratios of the high-activity ferrosoferric oxide-ammonium thiomolybdate-manganese oxide composite material prepared in Example 3 and ferrous oxide were set to 1:0, 1:1, and 0:1, respectively.
[0115] Figure 3 The following is a comparison chart of the degradation effects of the product prepared in Example 3 and ferrous oxide mixed in different proportions as a catalyst on COD. The experimental results show that the COD removed by the prepared high-activity ferrous oxide-ammonium thiomolybdate-manganese oxide composite material is almost equal to that of the ferrous oxide used in the traditional Fenton method when the dosage ratio is 1:1 and 0:1, indicating that the high-activity ferrous oxide-ammonium thiomolybdate-manganese oxide composite material can replace the ferrous oxide used in the traditional Fenton method to a certain extent. Since the high-activity ferrous oxide-ammonium thiomolybdate-manganese oxide composite material has a reusable effect, it provides feasibility for achieving low-cost use of heterogeneous Fenton technology.
[0116] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a highly active iron-based-sulfide-additive composite material, characterized in that: The following steps are involved: The iron-based material is added to the sulfide-additive solution, subjected to ultrasonic treatment, heated for reaction, and cooled to obtain a highly active iron-based-sulfide-additive composite material; Wherein, the auxiliary agent in the sulfide-auxiliary agent solution is selected from one of sulfite, sodium borohydride and manganese oxide.
2. The method for preparing the high-activity iron-based-sulfide-auxiliary composite material according to claim 1, characterized in that: The specific preparation method of the iron-based material comprises: adding an iron source and hydrogen peroxide into water, stirring evenly, adjusting the pH to neutral, standing, centrifuging, and drying to obtain the iron-based material.
3. The method for preparing the high-activity iron-based-sulfide-auxiliary composite material according to claim 2, characterized in that: The usage ratio of the iron source, hydrogen peroxide and water is (10-1000) mg: (1-20) mL: (10-1000) mL; and / or The iron source is selected from one of ferrous oxide, ferric oxide, ferroferric oxide, ferric chloride, ferric sulfate and ferrous sulfate; and / or The reagent used to adjust the pH is sulfuric acid; and / or The standing time is 1-1000 min.
4. The method for preparing the high-activity iron-based-sulfide-auxiliary composite material according to claim 1, characterized in that: The specific preparation method of the sulfide-additive solution comprises: adding a molybdenum source and a sulfur source into water, adding an additive after ultrasonic treatment, and continuing ultrasonic treatment to obtain the sulfide-additive solution.
5. The method for preparing the high-activity iron-based-sulfide-auxiliary composite material according to claim 4, characterized in that: The molybdenum source is selected from one or more of ammonium molybdate, sodium molybdate, molybdenum trioxide, molybdenum dioxide and molybdenum powder; and / or The sulfur source is selected from one or more of thioacetamide, thiourea, sulfur powder and sodium sulfide; and / or The molybdenum source, sulfur source, water and auxiliary agent are used in a ratio of (1-1000) mg: (1-2000) mg: (10-100) mL: (1-1000) mg; and / or The ultrasonic time is 1-60 min.
6. The method for preparing the high-activity iron-based-sulfide-auxiliary composite material according to claim 1, characterized in that: The ultrasonic treatment time is 1-100 min.
7. The method for preparing the high-activity iron-based-sulfide-auxiliary composite material according to claim 1, characterized in that: The heating reaction conditions are: reacting at 60-100° C. for 1-5 hours.
8. A high-activity iron-based-sulfide-additive composite material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the highly active iron-based-sulfide-auxiliary agent composite material as claimed in claim 8 in removing organic pollutants from wastewater.
10. A method for removing organic pollutants, characterized in that: The method comprises the following steps: putting the high-activity iron-based-sulfide-auxiliary composite material according to claim 8 into wastewater containing organic pollutants, adding an initiator, stirring, and achieving the removal of organic matter; wherein, The organic pollutant is phenol, and the concentration of phenol in the wastewater is 1-2000 mg / L; The initiator is 30wt% hydrogen peroxide; The input amount of the high-activity iron-based-sulfide-auxiliary composite material is 300 mg / L; The wastewater containing organic pollutants is acidic.
Citation Information
Patent Citations
Preparation method and application of iron-sulfur heterogeneous Fenton-like catalyst
CN105562036A
Composite ferroferric oxide and manganese dioxide Fenton catalyst and preparation method thereof
CN107570170A
High-activity iron-based-sulfide heterogeneous Fenton composite material and method for removing organic pollutants by using high-activity iron-based-sulfide heterogeneous Fenton composite material
CN113231082A